Literatur Keislaman Dalam Konteks Pesantren - Aisatun Nurhayati (IAIN Ponorogo, 2013)
Abstract: Literature in XV-XVIII century dominated by mysticism/tasawwuf, while in XIX it were multi disciplines, while in XX century it combinated and be more variatives. And the development of scolarship of “kitab kuning” (Islamic books) was slowler than social and natural sciencies. It was considered final from the Qur’an dan Hadits teachings, so it was sacral, complete and difficult to critic, and the students of Islamic Education be stagnant and less creative. Kitab kuning must be considered as a culture product, and had many falseness. It is a duty of Islamic Scholars (ulama) and we to revise this falseness.